2011
DOI: 10.4103/0019-5359.109901
|View full text |Cite
|
Sign up to set email alerts
|

Validity of simple, novel measures of generalized and central obesity among young Asian Indian women

Abstract: FMI was a better predictor of generalized obesity compared to BMI and BF%. Considering abdominal obesity as an independent risk factor for insulin resistance, both WC and WC/ht ratio were able to predict central obesity better than WHR. Finally, the study presents ranges for FFMI and FMI for various BMI categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…For example, a recent research conducted on Sri Lankan children showed strong fat mass correlations with BMI, WC, as well as hip circumference [15]. Another BC measurement study of young Asian Indian women found strong PBF correlations with BMI, WC, as well as WC to height ratio [16].…”
Section: Discussionmentioning
confidence: 97%
“…For example, a recent research conducted on Sri Lankan children showed strong fat mass correlations with BMI, WC, as well as hip circumference [15]. Another BC measurement study of young Asian Indian women found strong PBF correlations with BMI, WC, as well as WC to height ratio [16].…”
Section: Discussionmentioning
confidence: 97%
“…A study reported the body fat of Indian women (21-30 y) in the range of 13.9-40.6% with a mean value of 25.0% [15] while another study observed the body fat of Caucasian adult women in the range of 11.6 to 53.7% with a mean value of 28.7% [11]. Fat mass index is considered as a better predictor of generalized obesity compared to body mass index and percent body fat [16]. Fat mass Index (FMI) and Fat Free Mass Index (FFMI) can recognize whether the excess or de cit of body weight is due to the change of fat mass (FM) or fat free mass (FFM) or both and can provide information about actual body composition that may better re ect nutrition status [11].…”
Section: Discussionmentioning
confidence: 99%